Manual de acciones dirigidos a pacientes y trabajadores para evitar los efectos de las radiaciones en Imágenes Diagnosticas de Lorica E.U. (2022)
Ionizing radiation can come from radioactive materials that spontaneously emit this radiation or from man-made generators such as X-ray generators and particle accelerators that can cause negative health consequences. It is necessary to identify, evaluate, prevent and control the risk factors of ionizing radiation in departments where radiological diagnostic tests are carried out with physical structure, equipment and operation (risk diagnosis) in addition to periodic monitoring of risk factors. The main objective is to design a manual of actions aimed at patients, staff and workers, to avoid the effects of radiation on diagnostic images of Lorica E.U. In the methodology, a systematic review was implemented, the construction of an ionizing radiation protocol in which users and workers participated. It was concluded that the use of ionizing radiation is becoming more frequent. For this reason, apart from the fact that they are always exposed to a certain natural dose, the possibility of receiving radiation from artificial sources tends to increase.